(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
This chapter presents details of physical description, location, extent of erosion, method of access and previous work. Five structures and an enclosing wall were identified in the survey. There is no evidence to support the assertion that there is an early Christian presence on the stack. Pottery of Neolithic date was recovered during previous work.